Leveraging intercultural dialogue and collaborative learning to promote interpersonal and patient care competencies - Maysa Abuzant; Melissa Ann Labuda; Alia Gilbrecht-Hindi (Journal of Virtual Exchange)
This paper describes the virtual exchange (VE) between universities in the U.S. and in the West Bank, Occupied Palestinian Territories (oPt). The VE aimed at developing students’ interpersonal and patient health care practitioner communication skills through an intercultural dialogue framework. With this objective in mind, the program was designed to employ elements of both intercultural dialogue and team-based approaches to VE. Over the course of four weeks, students and facilitators met weekly via Zoom. During these live sessions, 26 students within their teams were engaged in a number of activities to share and learn about each other’s identities and cultural perceptions of mental health and practiced intercultural dialogue communication skills. Students also had to work collaboratively to explore different mental health case studies and how they are perceived within their communities through local interviews. The VE took into consideration the sociopolitical context of the students living under occupation, creating space for the participants to learn about one another’s daily lived reality including engaging in ad hoc dialogues on unexpected events happening in one of the countries. Data was collected through students’ reflections. Thematic analysis of the reflections revealed that the students reported interpersonal skills development and a culturally enriching experience for both the U.S. and West Bank, oPt students. Based on the findings a number of practical implications were drawn, including having a flexible program plan, facilitators meeting on a regular basis during the implementation phase and collecting students’ feedback throughout the program.